Mesenchymal Stem Cell-Derived Hepatocytes for Functional Liver Replacement - Christ, Bruno; Stock, Peggy (Frontiers in Immunology, 2012)
Mesenchymal stem cells represent an alternate cell source to substitute for primary hepatocytes in hepatocyte transplantation because of their multiple differentiation potential and nearly unlimited availability. They may differentiate into hepatocyte-like cells in vitro and maintain specific hepatocyte functions also after transplantation into the regenerating livers of mice or rats both under injury and non-injury conditions. Depending on the underlying liver disease their mode of action is either to replace the diseased liver tissue or to support liver regeneration through their anti-inflammatory and anti-apoptotic as well as their pro-proliferative action.